The Influence of the TGT (Teams Games Tournament) Learning Model on Table Tennis Learning Outcomes - Dony Andrijanto (Gladi : Jurnal Ilmu Keolahragaan, 2023)
The success or failure of students in learning can be influenced by several factors, one of which is the selection of the learning model to be used. The selection of learning models must be adapted to the characteristics of students. The learning model that is often used in the learning process is the cooperative learning model. There are several kinds of learning models that are often used, namely the TGT (Teams Games Tournament) learning model. The use of this learning model allows students to be active in learning, so as to improve student learning outcomes. This study aims to determine the effect of the TGT (Teams Games Tournament) learning model on table tennis learning outcomes. This research method uses a quasi-experimental design with one group pretest posttest. The population in the research is class students eight At school SMPN 5 Nganjuk which will be done 4 times. The sample used was 34 students. The data collection technique uses a table tennis stroke ability test. Data analysis techniques using descriptive analysis, normality test, and hypothesis testing. Based on the results of the analysis it can be concluded that there is a significant influence, this can be seen from the results of the analysis of hypothesis testing with a result of 0.00 which means <0.05. So it can be concluded that there is a significant influence using the TGT (Teams Games Tournament) learning model on table tennis learning outcomes.